1968
DOI: 10.1126/science.160.3825.322
|View full text |Cite
|
Sign up to set email alerts
|

DNA (Cell Number) and Protein in Neonatal Brain: Alteration by Maternal Dietary Protein Restriction

Abstract: Female rats were maintained on 8 or 27 percent protein diet by a pair-feeding schedule for 1 month before mating and throughout gestation. The brains of newborn rats from females on the 8 percent protein diet contained significantly less DNA and protein compared to the progeny of the females on the 27 percent diet. The data on DNA indicate that there are fewer cells; the protein content per cell was also lower. If, at birth, the brain cells are predominantly neurons, and their number becomes final at that time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
56
0
1

Year Published

1972
1972
2008
2008

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(68 citation statements)
references
References 14 publications
11
56
0
1
Order By: Relevance
“…During pregnancy this is associated with intrauterine growth retardation, particularly of extra-neural organs, with major alterations of lipid, carbohydrate and amino acid metabolism (Lee & Chow, 1965;Fain & Scow, 1966;Zamenhof, Van Marthens & Margolis, 1968; Chase, Dabiere, Welch & O'Brien, 1971 ; Tsoulos, Colwill, Battaglia, Makowski & Meschia, 1971 ; Thaler, 1972;Nitzan & Groffman, 1971;Widdowson, 1974). A similar growth retardation effect can be produced by modifying uterine blood flow to the placenta or umbilical blood flow to the fetus (Wigglesworth, 1964;Hohenauer & Oh, 1969;Emmanouilides, Townsend & Bauer, 1968;Roux, Tordet-Caridroit & Chanez, 1970;Hill, 1974).…”
Section: Maternal Metabolism and Fetal Growthmentioning
confidence: 99%
“…During pregnancy this is associated with intrauterine growth retardation, particularly of extra-neural organs, with major alterations of lipid, carbohydrate and amino acid metabolism (Lee & Chow, 1965;Fain & Scow, 1966;Zamenhof, Van Marthens & Margolis, 1968; Chase, Dabiere, Welch & O'Brien, 1971 ; Tsoulos, Colwill, Battaglia, Makowski & Meschia, 1971 ; Thaler, 1972;Nitzan & Groffman, 1971;Widdowson, 1974). A similar growth retardation effect can be produced by modifying uterine blood flow to the placenta or umbilical blood flow to the fetus (Wigglesworth, 1964;Hohenauer & Oh, 1969;Emmanouilides, Townsend & Bauer, 1968;Roux, Tordet-Caridroit & Chanez, 1970;Hill, 1974).…”
Section: Maternal Metabolism and Fetal Growthmentioning
confidence: 99%
“…More recent studies (Zamenhof, 1968) as well as by Winick (1968) have demonstrated that the deprivation is also accompanied by a reduction in brain cell number. This latter effect has been demonstrated too in human brain in infants who have died of severe early malnutrition (Winick and Rosso, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…The severest effects on total brain development in the neonatal rat are produced by undernutrition during gestation and lactation (18). At the time of weaning the undernourished neonatal rat manifests reduced neuronal and glial cell populations in the cerebrum, cerebellum, and brain stem.…”
mentioning
confidence: 99%